1997
DOI: 10.1164/ajrccm.156.1.9607090
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneities of Ventilation and the Diffusing Capacity to Perfusion in Various Chronic Lung Diseases

Abstract: Although impairment of gas exchange caused by ventilation-perfusion (VA/Q) mismatch has been extensively analyzed, there have been no systematic studies focused on determining the distributions of diffusion properties in dose connection with those of VA/Q. We attempted to clarify the simultaneous distributions of VA/Q and diffusion capacity to perfusion (D/Q) in patients with idiopathic pulmonary fibrosis (IPF) or chronic obstructive pulmonary disease (COPD). To assess pathologic determinants causing functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Although the causes of an obstructive pattern on PFTs are limited to the airway, a restrictive pattern on the PFTs can be secondary to parenchymal and/or nonparenchymal changes, both of which can be affected by many conditions common in our population, such as advanced malignant disease, thoracic radiation and/or chemotherapy, generalized muscle weakness, or spinal cord compression. The Dl CO reflects the availability of the pulmonarycapillary surface area and is affected by a number of factors, including alveolar membrane thickness, hemoglobin level, cardiac function, and heterogeneity of regional ventilation and perfusion (19,20). Reduction of the pretransplant Dl CO likely represents an abnormality in one or more of these factors, which can also be caused by advanced malignant disease, thoracic radia- For definition of abbreviations, see Table 6.…”
Section: Discussionmentioning
confidence: 99%
“…Although the causes of an obstructive pattern on PFTs are limited to the airway, a restrictive pattern on the PFTs can be secondary to parenchymal and/or nonparenchymal changes, both of which can be affected by many conditions common in our population, such as advanced malignant disease, thoracic radiation and/or chemotherapy, generalized muscle weakness, or spinal cord compression. The Dl CO reflects the availability of the pulmonarycapillary surface area and is affected by a number of factors, including alveolar membrane thickness, hemoglobin level, cardiac function, and heterogeneity of regional ventilation and perfusion (19,20). Reduction of the pretransplant Dl CO likely represents an abnormality in one or more of these factors, which can also be caused by advanced malignant disease, thoracic radia- For definition of abbreviations, see Table 6.…”
Section: Discussionmentioning
confidence: 99%
“…50,51 Reduction of the diffusion capacity can be due to compromise of any or a combination of these variables, leading to a reduction of the alveolar capillary interface. Unfortunately, the DL CO is the most variable parameter in a PFT, particularly when a restrictive or obstructive ventilatory impairment is present.…”
Section: Diffusion Capacitymentioning
confidence: 99%
“…49 However, it is known that although a lower alveolar volume, as found in patients with pulmonary disease, may decrease the diffusion capacity, the relationship is not in a 1:1 proportion. 48,51 In fact, several studies have demonstrated that in patients with known parenchymal lung diseases and low DL CO measurements, the alveolar volume corrected diffusion capacity often underestimated the reduction in diffusion capacity. 55,56 Therefore, the DL CO should not be corrected for alveolar volume.…”
Section: Diffusion Capacitymentioning
confidence: 99%
“…The assessment of lung ventilation (V)-perfusion (Q) imbalance in diseased lungs is important, since such imbalance significantly impairs alveolar gas-exchange function [1][2][3][4][5]. V/Q quotient single photon emission computed tomography (SPECT) derived from combined V-Q SPECT study is a useful tool for objective assessment and quantitation of lung V-Q imbalance on cross-sectional lungs [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with pulmonary emphysema traditionally had been believed to have grossly matched lung V-Q impairment, but significant V-Q imbalance may be present due to complicated lung pathophysiology such as alveolar destruction, compression of small vasculatures by hyperinflated lung tissue, and hypoxic vasoconstriction [13][14][15][16]. V/Q quotient SPECT may be sensitive to identify emphysematous lungs, as previous animal and clinical SPECT studies showed perfusion and/or ventilation impairment even in normal lungs on high-resolution computed tomography (CT) [4,9,[16][17][18][19]. Although emphysematous lung is usually assessed on morphologic CT, this SPECT may more accurately detect it.…”
Section: Introductionmentioning
confidence: 99%